Ernesto "Che" Guevara - Kellner, Douglas, 1943- (New York : Chelsea House Publishers, 1989)
Traces the life of the revolutionary who joined Castro's movement to overthrow Cuba's government, served as minister of industry, and was killed while leading a Communist guerrilla force in Bolivia.
Includes index.
Bibliography: p. 108.
Keywords: Guevara, Che, -- 1928-1967 -- Juvenile literature; Guevara, Che, -- 1928-1967.; Guerrillas -- Latin America -- Biography -- Juvenile literature; Guerrillas -- Latin America; Latin America -- Biography -- Juvenile literature; Latin America -- Politics and government -- 1948-1980.